A review on the entire installation process of dynamically installed anchors. (15th April 2020) - Han, Congcong; Liu, Jun
Abstract: This paper presents an overview of recent developments of the dynamically installed anchor (DIA), which is self-installed through its gravitational energy. Example results from the dynamic installation process and holding capacity of the DIA are highlighted, including the hydrodynamic characteristics of the anchor during free fall in water, anchor-soil-water interaction during dynamic installation in the seabed, and the anchor-mooring-line-soil interaction when the anchor is undergone uplift loading. On the basis of the present overview, simplified theoretical models are summarised to predict the entire installation process and holding capacity of the DIA. This paper describes design principles of the DIA and the current physical and numerical techniques analysing the anchor-mooring-line-soil-water interaction. Moreover, further development about the DIA is highlighted and advanced physical and numerical techniques solving the anchor-mooring-line-soil-water interaction are stated. Highlights: An overview of recent developments of the DIA is presented. Physical modelling and numerical simulations associated with the entire installation process of the DIA are highlighted. Novelty anchor types and advanced physical and numerical modelling are need to be developed in the future.